ASSESS THE REALITY OF FISCAL SUSTAINABILITY BETWEEN THE REQUIREMENTS OF FINANCIAL DISCIPLINE AND THE FINANCIAL IMBALANCE IN IRAQ-ANALYTICAL STUDY FOR THE PERIOD 2010–2020 - Asst. Prof. Dr. Ahmed. H. Al-Husayny (American Journals, 2024)
The major goal of the current study is to evaluate the financial sustainability of Iraq by looking at financial discipline guidelines on the one hand. However, to recognize and examine the root causes of the financial imbalance, it is common knowledge that nations like Iraq, which rely on a single resource to finance their economic operations, are developing financial sustainability policies and strategies by creating an agreement policy that will address both internal and external shocks. Increasing economic diversity through diversifying income sources, which promotes budgetary restraint and lowers budget deficit rates, enables organizations to better withstand shocks in the future. The study had two objectives, the first of which addressed the notion.
Keywords: Fiscal Sustainability, financial discipline, financial imbalance, internal and external shocks, financial imbalance, deficits in public budgets.